Controllable preparation method of CeSi2 / Al core-shell structure microspheres
Patent Information
- Application Number
- CN202611320184.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]为了解决上述现有技术中气相层积成本高、效率低,以及传统微流控法因铝壳层熔点限制而无法高温密实化核芯的难题问题,本发明提供了一种CeSi2/Al核壳结构微球的可控制备方法,本发明摒弃传统“一步法”策略,采用“先密实、后包覆”的分步策略:首先,利用微流体控制技术制备出不含铝壳层的CeSi2微球,并对其进行高温密实处理,使CeSi2核芯充分致密化,获得高密度、高强度的芯核;然后,将高密度CeSi2微球与含铝粉的分散介质混合,通过本发明设计的直线+波形微球排列管实现微球的单列有序聚焦,再经微流控三通装置,以二甲基硅油为连续相进行剪切包覆,形成核壳结构液滴,并经凝固浴固化、煅烧,最终得到壳层完整、核芯高密的CeSi2/Al核壳结构微球
[0017](1)本发明打破传统微流控法“一步包覆”再烧结的固有模式,先将不含铝壳层的CeSi2微球高温密实化后,获得高密度、高强度的致密化核芯,再于低温条件下完成铝壳层包覆与固化。该策略使核芯致密化与壳层成型过程分开,完全避免了铝壳层因高温处理而熔融的风险,解决了长期制约CeSi2/Al核壳结构微球密实化制备的技术瓶颈。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nuclear fuel research technology and relates to a controllable preparation method of CeSi2 / Al core-shell structured microspheres. Background Technology
[0002] In nuclear fuel research, non-radioactive silicon-cerium compounds are often used to simulate radioactive silicon-uranium compounds. Ce3Si2 and U3Si2 have similar crystal structures, so Ce3Si2 is often used to simulate the chemical properties of U3Si2. However, Ce3Si2 is difficult to synthesize and there are no commercially available products. Therefore, in the research on the manufacturing process of U3Si2 fuel elements, Ce3Si2, which has stable performance and is commercially available, is used to conduct relevant simulation studies.
[0003] Currently, the preparation of CeSi2 / Al core-shell structured microspheres mainly employs vapor deposition and traditional microfluidic methods. While vapor deposition can achieve shell coating, it suffers from high equipment costs, low deposition efficiency, and limited shell thickness, making it difficult to meet the needs of large-scale preparation. Traditional microfluidic methods use an aqueous phase containing CeSi2 powder as the core fluid and an oil phase containing aluminum powder as the shell fluid, utilizing the immiscibility of water and oil to form core-shell structured droplets, which are then solidified and sintered to obtain CeSi2 / Al core-shell structured microspheres. However, this method has a fundamental flaw: during the sintering process, although the low-temperature stage (approximately 600℃) can remove organic matter and moisture, the resulting microspheres have low density and a loose structure, rendering them impractical; if the temperature is further increased to 1000-1500℃ to achieve densification, the aluminum powder in the shell (melting point approximately 660℃) will melt, destroying the shell structure and preventing the acquisition of high-density core-shell structured microspheres. Therefore, existing technologies cannot simultaneously achieve core compaction and shell integrity, and there is an urgent need to develop a controllable preparation method that can achieve high core compaction while maintaining the stability of the aluminum shell structure. Summary of the Invention
[0004] To address the problems of high cost and low efficiency in existing technologies, and the inability of traditional microfluidic methods to densify the core at high temperatures due to the melting point limitation of the aluminum shell, this invention provides a controllable preparation method for CeSi2 / Al core-shell structured microspheres. This invention abandons the traditional one-step strategy and adopts a step-by-step strategy of "densification first, then coating": First, CeSi2 microspheres without an aluminum shell are prepared using microfluidic control technology and subjected to high-temperature densification treatment to fully densify the CeSi2 core, obtaining a high-density, high-strength core. Then, the high-density CeSi2 microspheres are mixed with a dispersion medium containing aluminum powder. The microspheres are then focused in a single row using a linear + wave-shaped microsphere arrangement tube designed in this invention. Finally, the mixture is sheared and coated with dimethyl silicone oil as the continuous phase through a microfluidic three-way device to form core-shell structured droplets. These droplets are then solidified and calcined in a coagulation bath to obtain CeSi2 / Al core-shell structured microspheres with an intact shell and a high-density core. This method effectively avoids the limitation of high-temperature melting of the aluminum shell, achieves independent control of core density and shell morphology, and can precisely control shell thickness by adjusting the flow rate ratio of the continuous phase to the dispersed phase. It has good process repeatability and prospects for large-scale application. Specifically, it includes the following methods:
[0005] Step 1: Mix CeSi2 microspheres with CMC-PVA-aluminum powder dispersion medium to achieve a CeSi2 microsphere volume fraction of 5%, and stir until homogeneous to obtain the dispersed phase.
[0006] Preferably, the CeSi2 microspheres have a particle size of 100-600 μm and a density of 4-5 g / cm³. 3 Most preferably, the CeSi2 microspheres have a particle size of 280 μm and a density of 4.5 g / cm³. 3 .
[0007] Preferably, the CMC-PVA-aluminum powder dispersion medium comprises, by mass percentage, 1.5-2% sodium carboxymethyl cellulose (CMC-Na), 0.5-5% polyvinyl alcohol (PVA), and 15% aluminum powder, with the balance being water. Most preferably, the mass percentage of CMC-Na is 1.7%, and the mass percentage of PVA is 2.5%.
[0008] The most preferred method for preparing the CMC-PVA-aluminum powder dispersion medium is as follows: water and aluminum powder are mixed in a sand mill and dispersed at 200 rpm for 30 min. During the dispersion, ice water is continuously introduced into the cooling jacket of the sand mill to control the temperature (controlled at 0℃). The resulting aluminum powder dispersion is then mixed with PVA solution and CMC-Na solution respectively. Each component is adjusted to the target mass fraction, and the mixture is stirred continuously at 0-5℃ for 15 min until the system is completely homogeneous.
[0009] Step 2: The dispersed phase flows sequentially through the straight + wave-shaped microsphere arrangement tube and the capillary. After the dispersed phase flows out of the capillary, it is sheared by the continuous phase in the three-way valve to form core-shell structured droplets, and then flows out through the outlet pipe into the coagulation bath. The three-way valve is sleeved on the capillary, and the straight + wave-shaped microsphere arrangement tube is placed vertically.
[0010] Preferably, the continuous phase is dimethyl silicone oil.
[0011] Preferably, the coagulation bath comprises, by weight percentage, 74-75% dimethyl silicone oil, 24-25% isoamyl alcohol and 1% boric acid.
[0012] Preferably, the flow rate ratio of the continuous phase to the dispersed phase is 6-10, and most preferably 8.
[0013] Preferably, the linear + wave-shaped microsphere arrangement tube is a polytetrafluoroethylene tube with an outer diameter of 1600 μm and an inner diameter of 1000 μm, and is composed of a horizontal linear tube and a sinusoidal wave tube. The dispersed phase flows in through the horizontal linear tube and flows out through the sinusoidal wave tube. Most preferably, the length of the horizontal linear tube is 20 cm, and the lengths of the rising and falling sections of the sinusoidal wave tube are both 25 cm, with an included angle of 60° in the horizontal direction.
[0014] Preferably, the capillary is a glass tube with an outer diameter of 670 μm and an inner diameter of 450 μm; the tee is a T-type tee, with the continuous phase flowing in from the vertical port; and the outlet tube is a polytetrafluoroethylene tube with an outer diameter of 1600 μm and an inner diameter of 1000 μm.
[0015] Step 3: The outflowing core-shell structure droplets gradually settle in the coagulation bath. The PVA in the shell undergoes cross-linking and solidification with boric acid. After standing for 1 hour, the shell is completely solidified. The mixture is filtered to remove the filtrate. The precipitate is washed sequentially with petroleum ether and anhydrous ethanol to obtain CeSi2-loaded gel microspheres. The gel microspheres are then air-dried indoors for 24 hours to remove some petroleum ether, ethanol, and free water. Under inert gas protection (to prevent oxidation of aluminum powder in the shell), the microspheres are placed in a tube furnace for calcination. The temperature is increased to 150°C at a rate of 2°C / min and held for 2 hours to remove bound water from the gel. The temperature is then increased to 350°C at a rate of 5°C / min, and then increased to 500°C at a rate of 1°C / min and held for 2 hours to completely break down the PVA chains in the gel. During this stage, the organic matter decomposes and releases a large amount of gas, so the heating rate must be strictly controlled to prevent the microspheres from rupturing. The temperature was then increased to 650℃ at a rate of 5℃ / min and held for 1 hour to allow the aluminum shell to complete its final shrinkage, resulting in high-density CeSi2 / Al core-shell structured microspheres.
[0016] The present invention has the following advantages:
[0017] (1) This invention breaks away from the traditional microfluidic method of "one-step coating" followed by sintering. First, CeSi2 microspheres without an aluminum shell are densified at high temperature to obtain a high-density, high-strength densified core. Then, the aluminum shell is coated and solidified at low temperature. This strategy separates the core densification process from the shell forming process, completely avoiding the risk of the aluminum shell melting due to high-temperature treatment, and solving the long-standing technical bottleneck restricting the densification preparation of CeSi2 / Al core-shell structure microspheres.
[0018] (2) The linear + wave-shaped microsphere arrangement tube designed in this invention utilizes a horizontal linear segment to achieve radial single-layer focusing of microspheres. It leverages the alternating compression and stretching effects of the rising and falling segments in the wave-shaped undulations on the microsphere spacing, combined with the synergistic control of wall effect lift, lubrication repulsion, and far-field hydrodynamics, to homogenize the initially disordered distribution of microspheres after two stages of waveform control. This structure requires no external electric or magnetic field; it achieves a stable, single-row, ordered arrangement of high-density, large-diameter microspheres solely through the coupling of the flow channel configuration and the gravitational field, providing a crucial prerequisite for subsequent precise coating.
[0019] (3) This invention can conveniently control the diameter of the loaded droplets and the corresponding shell thickness by adjusting the flow rate ratio of the continuous phase to the dispersed phase in the microfluidic coating station. The larger the flow rate ratio, the smaller the droplet diameter and the thinner the shell; conversely, the shell becomes thicker. Under the optimal flow rate ratio, core-shell structured microspheres with an average particle size of 310 μm, a shell thickness of 35 μm, a particle size variation coefficient CV of 4.5%, and a sphericity of 1.04 can be stably obtained, exhibiting good monodispersity and repeatability.
[0020] (4) Compared with the high-vacuum deposition equipment and complex process control required by the vapor deposition method, the present invention is based on conventional microfluidic devices and tubular furnace calcination process, which requires less equipment investment and is easy to operate. The preparation of the dispersion medium and the focusing, arrangement, coating and solidification of microspheres can be completed under conventional experimental conditions. The process window is wide and the repeatability is good, which has good industrialization prospects.
[0021] (5) The CeSi2 / Al core-shell structured microspheres prepared in this invention exhibit high density and strength after high-temperature pre-sintering. The shell layer is fully formed after low-temperature calcination (up to 650℃). Al elements are uniformly distributed in the shell layer region, while Ce and Si elements are concentrated in the core region. The core-shell interface is clear, without an intermediate reaction layer, and exhibits good interfacial compatibility. The average apparent density of the microspheres reaches 3.27 g / cm³. 3 With a relative density of 81.1%TD, controllable shrinkage, and a porous morphology in the shell that is conducive to subsequent melting and infiltration, it can directly meet the performance requirements of U3Si2 / Al simulated fuel research.
[0022] (6) The present invention uses two high-density particles with different densities, alumina microspheres and CeSi2 microspheres, to verify the method of the present invention. The results show that the method of the present invention has good focusing arrangement and coating effect, indicating that the technical solution can be extended to the preparation of other high-density core / metal shell core-shell structure microspheres, and has broad application prospects. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0024] Figure 1 This is a structural diagram of the linear + wave-shaped microsphere array tube for Experiment Example 1.
[0025] Figure 2 Microspheres were used for the experimental example. Figure 2 (a) CeSi2 microspheres Figure 2 (b) is alumina microspheres.
[0026] Figure 3 This is a schematic diagram of the forces acting on the microsphere.
[0027] Figure 4 Fitted rheological curves for CMC-Na solutions of different concentrations.
[0028] Figure 5 The sedimentation time of alumina microspheres in CMC-Na solutions of different concentrations is given.
[0029] Figure 6 This study investigates the focusing behavior of alumina microspheres in dispersions of different concentrations. Figure 6 (a) is 1.5 wt%; Figure 6 (b) is 1.75 wt%; Figure 6 (c) is 2.0 wt%.
[0030] Figure 7 This describes the focusing and aligning process of CeSi2 microspheres in different sections of the flow channel. Figure 7 (a) is the flow channel inlet; Figure 7 (b) is a horizontal segment; Figure 7 (c) represents the first fluctuating upward segment; Figure 7 (d) represents the first fluctuating and descending segment; Figure 7 (e) is the rising segment of the second fluctuation segment; Figure 7 (f) is the second fluctuating segment, the descending segment.
[0031] Figure 8This is a graph showing the variation of the microsphere spacing and its coefficient of variation with the location of the pipe section.
[0032] Figure 9 Flowchart for the preparation of CeSi2 / Al core-shell structured microspheres.
[0033] Figure 10 This is a diagram of the apparatus used to prepare CeSi2 / Al core-shell structured microspheres.
[0034] Figure 11 This is a diagram illustrating the calcination heating mode.
[0035] Figure 12 This is a schematic diagram of the loaded droplet conversion process.
[0036] Figure 13 Rheological curves for different proportions of dispersion media.
[0037] Figure 14 For the loaded droplet diagram, Figure 14 (a) is v c / v d =10; Figure 14 (b) is v c / v d =8; Figure 14 (c) is v c / v d =6.
[0038] Figure 15 For v c / v d The effect of this effect on the diameter of the gel microspheres.
[0039] Figure 16 This is an electron micrograph of the cross-section of the gel microspheres. Figure 16 (a) is vc / vd=10; Figure 16 (b) is vc / vd=8; Figure 16 (c) is vc / vd=6.
[0040] Figure 17 The image shows the morphology of CeSi2 / Al core-shell microspheres. Figure 17 (a) is an optical micrograph; Figure 17 (b) is a scanning electron microscope image.
[0041] Figure 18 EDS elemental analysis diagram of CeSi2 / Al microsphere cross section. Figure 18 (a) is a cross-sectional topographic image; Figure 18 (b) is the distribution image of Al elements. Figure 18 (c) is the distribution image of Ce elements; Figure 18 (d) is the distribution image of Si element. Detailed Implementation
[0042] The technical solutions in the embodiments of the invention are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0043] Experimental Example 1
[0044] This experimental example uses a straight-line + wave-shaped microsphere array tube to conduct a microsphere hydraulic focusing arrangement experiment. The main body of the device consists of a complete polytetrafluoroethylene (PTFE) cylindrical tube (outer diameter 1600 μm, inner diameter 1000 μm) bent and fixed into a straight-line + wave-shaped structure, placed in a vertical plane with a length l1 of 20 cm. A sinusoidal wave-shaped tube section is connected after the horizontal tube section, with the horizontal length l2 of both the rising and falling sections being 25 cm, and the angle with the horizontal direction being θ = 60°. The device structure is as follows. Figure 1 As shown.
[0045] During the experiment, the microspheres and the dispersion medium (1.5-2.5% CMC-Na solution by mass concentration) were injected into the channel through the inlet by a constant flow injection pump. Under pressure, the microspheres were carried through the straight section and the wave section in sequence, and finally flowed out from the outlet.
[0046] The microspheres used in this experimental example and the following experimental examples are as follows:
[0047] 280 μm, coefficient of variation of particle size of 2.6%, density of 4.5 g / cm³ 3 CeSi2 microspheres with a diameter of 280 μm and a density of 3.9 g / cm³ 3 The alumina microspheres were surface-cleaned to remove impurities before use, and then hydrophilically modified with glycerol. Glycerol molecules adsorb onto the microsphere surface via hydrogen bonds formed by their hydroxyl groups, introducing hydrophilic groups and thus improving the wettability and dispersion stability of the microspheres in aqueous systems. Figure 2 As shown.
[0048] During the experiment, microscopic imaging was used to observe and record the alignment behavior of microspheres at different positions in the flow channel in real time, acquiring images of their motion trajectory within straight and wave segments. Based on the motion video data, image analysis was performed using Tracker software to extract key motion parameters such as microsphere trajectory, instantaneous velocity, and center-to-center distance, providing quantitative basis for subsequent microsphere alignment behavior analysis. A rotational rheometer was used to measure the viscosity parameters of the CMC-Na solution at different shear rates. The shear rate-viscosity curve was fitted using Origin software based on a simplified form of the Bird-Carreau constitutive equation (Equation 1).
[0049] ηeff =η0[1+(λγ) 2 ] (n-1) / 2
[0050] In the formula η eff γ is the apparent viscosity, Pa·s; γ is the shear rate, s. -1 η0 is the zero shear viscosity, Pa·s; λ is the characteristic time, s; n is the power law exponent, which characterizes the degree of shear thinning and usually takes a value between 0 and 1.
[0051] High-density microspheres are randomly dispersed in a non-Newtonian fluid (CMC-Na solution) dispersion medium. When the dispersed phase flows through... Figure 3 When the straight and wave-shaped microspheres are arranged in the tube, the forces acting on the disordered microspheres (segment a1) in different configuration tubes change differently, causing dynamic changes in the speed and spatial position of the microspheres in the tube.
[0052] In a horizontal straight pipe (section a2), the various forces acting on the microsphere are as follows: Figure 3 As shown. After the microspheres enter the horizontal section with the dispersion medium, the axial viscous resistance causes them to quickly match the fluid velocity, and they maintain a uniform axial velocity due to inertia. Radially, due to the shear-thinning properties of the dispersion medium, the local effective viscosity (η) of the dispersion medium... eff The reduction of radial viscous resistance F on the microspheres results in a decrease in the radial viscous resistance F. d (Equation 2) decreases, increasing the microsphere settling force F. sed (Equation 3) and F d The difference in the value of the sedimentation rate of the microspheres accelerates during this stage.
[0053] Equation 2: F d =3πηd p Δu
[0054] Formula 3: F sed =π·d p 3 (ρ p -ρ f )g / 6
[0055] In the formula, d p ρ is the diameter of the microsphere, in meters (m); p ρ f Densities of the microspheres and the fluid, respectively, in kg / m³. 3 ;Δu=u f -u p ρ is the velocity difference between the fluid and the microsphere, in m / s; g is the acceleration due to gravity.
[0056] When the microspheres settle into the near-wall region, the presence of the wall causes an asymmetry in the flow field around them, thus generating a lift force pointing towards the center of the flow channel—the wall effect lift F. w :
[0057] Formula 4: F w =C w (η eff Ud p 2 ) / h α
[0058] Where C w α is a proportionality constant; U is the characteristic velocity, m / s; h is the distance between the microsphere surface and the wall, m; α is an exponent greater than 1.
[0059] F w Closely related to h, as the microspheres approach the bottom of the tube, F w As h gradually decreases, it increases rapidly without becoming nonlinear, until h decreases to a certain critical value h. eq Afterwards, with F d F sed The radial equilibrium is reached as shown in equation (5). The microsphere swarm collectively follows this equilibrium mechanism, achieving stable single-row focusing within an extremely thin flow layer at the bottom of the tube, as... Figure 4 As shown.
[0060] Formula 5: F sed =F w +F d
[0061] Entering the ascending phase (segment a3), the forces acting on the microsphere are shown below. Figure 3 F sed Axial component of force F sed,ax The direction is opposite to the fluid flow direction, and the change in force on the microspheres causes a change in the spacing between the microspheres. Compared to ρ p In smaller dispersions, the sedimentation acceleration period of particles in high-density, large-diameter particle dispersions is significantly increased. The increase in Δu causes the rear microspheres to generate a positive relative velocity with respect to the front microspheres, resulting in a larger spacing between microspheres (a≫d). p The spacing 'a' of the microspheres is continuously compressed. When the spacing 'a' ≪ d p At that time, the liquid film within the gap is compressed, generating the lubricating repulsive force F according to Equation 6. lub This force increases sharply as a decreases, thus maintaining the minimum spacing between the microspheres.
[0062] Formula 6: F lub =C1η eff d p 2 Δu / a
[0063] In the formula, C1 is a proportionality constant.
[0064] When the microsphere enters the descent segment (segment a4), F sed,axThe direction of motion is the same as the flow direction, providing additional driving force. At this point, the microspheres will accelerate, with the forward microspheres responding faster than the backward ones, and the spacing 'a' is stretched axially. However, as the microsphere velocity gradually increases and exceeds the fluid velocity, F... d The velocity increases gradually in the opposite direction to the fluid flow direction until the microspheres reach a constant velocity stage. Simultaneously, the microspheres, moving in a single file within the shear flow field of the flow channel, are also subjected to far-field hydrodynamic forces F. hyd The effect (Equation 7), F hyd The distance between the microspheres increases as the spacing between them increases, allowing the microspheres to reach a constant speed in a shorter time.
[0065] Formula 7: F lub =C h η eff γd p 2 Φ(a / d p )
[0066] In the formula, C h Φ(a / d) is a proportionality constant. p ) is a dimensionless attenuation function for spacing, and its range of action can reach several particle sizes.
[0067] This experiment employs a 60° flow channel angle design. This angle, determined based on preliminary experimental optimization, achieves a balance between axial gravity separation and radial inertial focusing, enabling efficient adjustment of the microsphere spacing. The microsphere spacing adjustment effect is optimal when the angle is 60°.
[0068] Experimental Example 2
[0069] The viscosity of the dispersion medium affects both the sedimentation stability of the dispersed phase in the storage container and the viscous resistance and wall effect lift experienced by the microspheres flowing in the pipeline, making it a key parameter for controlling the aggregation and alignment of microspheres. CMC-Na solution exhibits a high zero-shear viscosity (η0) during static storage, effectively suppressing microsphere sedimentation. When flowing within a channel, its apparent viscosity decreases with increasing flow shear rate, reducing flow resistance and maintaining the force balance environment required for aggregation and alignment. To systematically investigate the effect of dispersion medium viscosity on microsphere aggregation, the rheological properties of CMC-Na aqueous solutions with different concentrations (1.5-2.5 wt%) were first characterized, such as... Figure 4 As shown in Table 1, Table 1 gives the corresponding fitting parameters for the simplified Bird-Carreau model.
[0070] Table 1. Fitting parameters of the Bird-Carreau model for CMC-Na solutions of different concentrations.
[0071] <![CDATA[η0 / mPa·s]]> 1592 3264 4043 6132 10394 λ / s 0.965 1.182 1.075 1.228 1.780 n 0.735 0.708 0.682 0.660 0.647 <![CDATA[R 2 ]]> 0.99989 0.99818 0.99871 0.99465 0.9965
[0072] Depend on Figure 4As shown in Table 1, the zero-shear viscosity η0 of the solution increases significantly with increasing CMC-Na concentration, rising from 1592 mPa·s at 1.5 wt% to 10394 mPa·s at 2.5 wt%. When the CMC-Na concentration increases from 1.5% to 2.0%, η0 increases from 1592 to 4043, an increase of approximately 154%; while when it increases from 2.0% to 2.5%, η0 surges from 4043 to 10394, an increase of 158%.
[0073] CMC-Na solutions at all concentrations exhibited typical shear-thinning characteristics, with a power-law exponent n ranging from 0.65 to 0.74. The closer the n value is to 1, the closer the fluid behaves to Newtonian behavior; the smaller the n value, the stronger the shear-thinning. Table 1 shows that the n value generally decreases with increasing concentration: n = 0.735 at 1.5%, n = 0.66 at 2.0%, and n = 0.647 at 2.5%. This pattern can be explained from the perspective of molecular motion: at low concentrations, molecular chains are less entangled, and the chain segment orientation is limited under shear, resulting in a less significant decrease in viscosity; as the concentration increases, the entanglement network becomes denser, and shear causes the entanglement points to dissociate, aligning the molecular chains along the flow direction, leading to a greater decrease in viscosity. The overall trend still conforms to the principle that higher concentrations result in stronger shear-thinning.
[0074] The viscosity of the dispersion medium is a key parameter for controlling the aggregation and alignment behavior of microspheres. It affects both the sedimentation stability of the dispersion during storage and the magnitude of the viscous resistance and wall effect lift experienced by the microspheres in the pipeline. This experiment used a high degree of substitution (DS=1.2) and medium-to-high molecular weight (M... w 2.5×10 5 CMC-Na, as a dispersion medium, exhibits typical pseudoplasticity in its aqueous solution, displaying significant shear-thinning characteristics. CMC-Na solutions exhibit a high zero-shear viscosity η0 during static storage, effectively suppressing microsphere sedimentation; when flowing within the channel, the apparent viscosity η... eff The viscosity decreases with increasing shear rate, which reduces flow resistance and maintains the force balance environment required for focused alignment. This "static high viscosity, dynamic low viscosity" characteristic makes it an ideal dispersion medium for this study.
[0075] Experimental Example 3
[0076] Because the yield of monodisperse microspheres prepared from ultrafine CeSi2 powder using microfluidic technology is low and the activity is high, and there are certain operational risks, this experiment used commercially available monodisperse alumina microspheres as model particles. Under the same particle size conditions, Al2O3 microspheres and CeSi2 microspheres exhibit similar sedimentation behavior characteristics, and their aggregation and arrangement patterns can serve as the basis for subsequent verification experiments and demonstrate the universality of their application to high-density particles.
[0077] This experiment determined the complete settling time of alumina microspheres at different concentrations, using a designed operating time of t0=30min as a control. The results are as follows: Figure 5 As shown. For alumina microspheres, the complete settling time of the microspheres can exceed the expected running time t0 only when the CMC-Na concentration is higher than 1.75wt%, thus ensuring that the microspheres enter the pipeline relatively stably and uniformly during the experiment.
[0078] The running time of the sedimentation characteristic matching experimental device is only an external constraint. The actual focusing performance of the microspheres in the dispersion medium is the ultimate basis for determining the appropriate viscosity. Figure 6 The focusing behavior of 5% (v / v) alumina microspheres in horizontal sections of CMC-Na solutions at different concentrations was demonstrated. When the CMC-Na concentration was 1.5 wt% (η0 = 3264 mPa·s), the viscous resistance was low and insufficient to effectively suppress sedimentation force, causing the microspheres to settle too quickly and accumulate in the horizontal section of the pipe. At a concentration of 1.75 wt% (η0 = 4043 mPa·s), the microspheres entered the pipe uniformly with the dispersion medium, achieving complete focusing and a single-row arrangement. When the concentration increased to 2.0 wt% (η0 = 6132 mPa·s), although the sedimentation stability of the microspheres was higher, the increased viscous resistance caused excessive suspension, making radial focusing difficult. This result is consistent with the sedimentation time screening conclusion, namely, for alumina microspheres, the suitable zero-shear viscosity of the CMC-Na solution is approximately η0 = 3264 mPa·s.
[0079] Under the same experimental conditions, CeSi2 microspheres can be stably focused and form a single-row arrangement when using a CMC-Na solution with η0 = 4043 mPa·s (i.e., 2.0 wt%).
[0080] Test Example 4
[0081] Based on the determination of the optimal dispersion medium concentration (viscosity), the actual focusing and alignment behavior of microspheres in a straight + wavy flow channel was further investigated. This experiment used a 2.0 wt% CMC-Na solution as the dispersion medium to conduct a focusing and alignment experiment on CeSi2 microspheres with a volume fraction of 5%, at a flow rate of 150 μL / min. The motion state and spacing changes of the microspheres in each stage of the flow channel were observed. The results are as follows: Figure 7-8 As shown.
[0082] Figure 7The evolution of CeSi2 microspheres' focused arrangement within different sections of the flow channel was demonstrated. In the inlet section, the microspheres were randomly arranged. At the end of the horizontal straight section, the microspheres had completed radial focusing, forming a single row at the bottom of the tube, but with significant differences in spacing. Entering the first undulating upward section, the microsphere spacing was continuously compressed, especially for microspheres with larger gaps; entering the first undulating downward section, the spacing was stretched, with the overall spacing slightly larger than in the upward section. After adjustment in the first undulating section, the microsphere spacing was initially homogenized; the second undulating section further corrected the remaining deviations, ultimately forming a uniformly spaced single row at the outlet. Observations of Al2O3 microspheres were consistent with this, indicating that this method has good applicability to particles of different densities.
[0083] To quantify the effect of microsphere spacing homogenization, Tracker software was used to track the movement trajectory of CeSi2 microspheres, statistically analyze the average velocity and spacing 'a' of the pipe section, and calculate the coefficient of variation (CV). Within the straight-line + wavy flow channel, the microspheres exhibited a characteristic velocity variation of deceleration during the rising phase (3.1 mm / s) and acceleration during the falling phase (5.2 mm / s) (horizontal velocity 4.3 mm / s). This measured velocity data highly agrees with the theoretical force analysis results. Figure 8 Given the particle size d p The dimensionless spacing 'a' and CV vary with the pipe section position. The average spacing of the initially randomly distributed microspheres after radial focusing through the straight section is 2.4d. p CV=67.7%, which decreased to 1.8d after the first fluctuation period adjustment. p The CV was 38.2%, and after a second correction in the second fluctuation phase, it stabilized at 1.5d. p The lateral velocity (CV) was significantly reduced to 9.6%, and the spacing homogenization effect was significant. These results indicate that a straight-line + wave-shaped flow channel can achieve stable control over the transformation of high-density, large-diameter microspheres from disordered dispersion to highly ordered monolayer focusing and arrangement through the synergistic effect of the flow field and the gravitational field.
[0084] Experimental Example 5
[0085] This experimental example uses the cross-linking reaction of PVA and boric acid as the shell solidification mechanism. The hydroxyl groups on the PVA molecular chain form dynamic borate ester bonds with boric acid in aqueous solution, constructing a three-dimensional network structure and achieving gelation.
[0086] Since the continuous phase in this experiment is dimethyl silicone oil, an oil-based coagulation bath scheme was selected, consisting of 1.00 wt% boric acid, 24.5 wt% isoamyl alcohol, and 74.5 wt% dimethyl silicone oil. Isoamyl alcohol, acting as a co-solvent, dissolves both boric acid and dimethyl silicone oil, ensuring that the composition of the coagulation bath is essentially consistent with that of the continuous phase. This guarantees the stability of the droplet morphology during shear formation and coagulation. When the dispersed phase droplets enter the coagulation bath, the residual dimethyl silicone oil film on the droplet surface dissolves in the isoamyl alcohol, eliminating the mass transfer barrier and ensuring a uniform reaction between PVA and boric acid, thereby obtaining gel microspheres with good sphericity.
[0087] The specific preparation method of CeSi2 / Al core-shell structured microspheres is as follows ( Figure 9 ):
[0088] Step 1: Mix water and aluminum powder in a sand mill and disperse at 200 rpm for 30 min. During dispersion, continuously circulate ice water into the cooling jacket of the sand mill to control the temperature (0℃). Thoroughly mix the resulting aluminum powder dispersion with the PVA solution, then add CMC-Na solution to adjust each component to the target mass fraction. Stir continuously at 0-5℃ for 15 min until the system is completely homogeneous to obtain the dispersion medium used for microsphere focusing and arrangement. Add CeSi2 microspheres at a volume fraction of 5% to the dispersion medium and disperse and mix thoroughly to obtain the dispersed phase.
[0089] Step two: The dispersed phase is injected into the linear + wave-shaped flow channel at an initial flow rate of 200 μL / min using a constant flow injection pump. After the feed liquid passes through the focusing and aligning section for spacing control, it enters the microfluidic shell coating section as the dispersed phase. By adjusting the flow rate of the continuous phase, droplets loaded with CeSi2 microspheres are generated through shearing. The droplets then enter the coagulation bath through the outlet pipe. Figure 10 As shown.
[0090] Step 3: During sedimentation, the PVA in the shell gradually cross-links and solidifies with boric acid. After standing for 1 hour to allow complete solidification of the shell, the product is repeatedly washed with petroleum ether and anhydrous ethanol to obtain CeSi2-loaded gel microspheres. To prevent gel cracking of the shell, the gel microspheres are air-dried indoors for 24 hours to allow the petroleum ether, ethanol, and free water in the gel to evaporate naturally. The gel microspheres are then calcined in a tube furnace using the following heating procedure: Figure 11 As shown, the temperature was increased to 150℃ at a rate of 2℃ / min and held for 2 hours. Then, it was increased to 350℃ at a rate of 5℃ / min, and then to 500℃ at a rate of 1℃ / min and held for 2 hours. Finally, it was directly heated to 650℃ at a rate of 5℃ / min and held for 1 hour. The entire calcination process was carried out under a nitrogen atmosphere to prevent oxidation of the aluminum powder in the shell, resulting in high-density CeSi2 / Al core-shell structured microspheres. The droplet transformation process is as follows... Figure 12 As shown.
[0091] The viscosity of the dispersion medium is a key factor in controlling the focused alignment of microspheres within microchannels. To achieve shell coating of the CeSi2 core and ultimately prepare CeSi2 / Al core-shell structured microspheres, the dispersion medium must fulfill a dual function: ensuring stable focused alignment of the CeSi2 microspheres and serving as the shell fluid for subsequent droplet loading. Therefore, a composite dispersion medium needs to be prepared by introducing the shell material (Al powder) and the gel component PVA into a CMC-Na solution.
[0092] This experiment investigated the performance changes of CMC-Na solution after adding a fixed amount of PVA and aluminum powder. Three groups of dispersions with different CMC-Na / PVA ratios were prepared, and the distribution of each group is shown in Table 2. A 2wt% CMC-Na solution (group a) was used as the rheological performance reference. Furthermore, to verify whether the composite dispersion medium containing aluminum powder and PVA could still meet the rheological requirements for microsphere focusing and arrangement, the apparent viscosity-shear rate curves of formulations b, c, and d were measured and compared with those of group a. The results are shown in Table 2. Figure 13 As shown.
[0093] Table 2. Components and proportions of the dispersion medium
[0094] a 2.00% - - 98.00% b 1.50% 5.00% 15.0% 78.50% c 1.70% 2.50% 15.0% 80.80% d 1.90% 0.50% 15.0% 82.60%
[0095] Comparison of the rheological curves of the four dispersion media revealed that three of the composite dispersion media exhibited typical shear-thinning characteristics, consistent with the rheological behavior of the control group (group a). Specifically, group b showed significantly lower viscosity at all shear rates than the control group, with a smaller viscosity decrease in the high-shear region, indicating that the high concentration of PVA (5wt%) interfered with the shear orientation of the CMC-Na molecular chains, significantly weakening the shear-thinning properties. Group c had slightly lower overall viscosity than the control group, with larger deviations in the low and medium shear regions, but its shear-thinning trend was basically consistent with the control group. The rheological curve of group d highly overlapped with the control group, showing the smallest deviation (<5%) across the entire shear rate range. This indicates that, while maintaining a constant CMC-Na concentration, the introduction of low-concentration PVA (0.5%) and aluminum powder caused only a slight viscosity shift, making it theoretically the optimal solution from a rheological consistency perspective.
[0096] Further analysis using the aforementioned composite dispersion media to prepare droplets individually revealed that the droplet formation in group b was unstable, easily shifting from a dripping pattern to a jetting pattern. This was attributed to the higher PVA content, which increased the viscoelasticity and decreased the surface tension of the medium, making it less susceptible to shearing by the continuous phase. Groups c and d both achieved good droplet formation, but the droplets prepared in group d gelled more slowly in the coagulation bath, easily fusing together before complete solidification, resulting in decreased sphericity and insufficient strength of the gel microspheres. This was attributed to the lower PVA content, which hindered the formation of a stable gel framework.
[0097] In summary, the viscosity and shear thinning behavior of the water-based dispersion system mainly composed of CMC-Na are dominated by its concentration. The addition of low-concentration PVA (≤2.5%) and rigid aluminum powder only causes a slight shift in viscosity, and the rheological properties can be precisely matched by fine-tuning the CMC-Na concentration. However, too low a PVA concentration will weaken the gelation performance; while a high PVA concentration (≥5%) will significantly change the shear thinning behavior. Considering both rheological matching and curing effect, the dispersion group C (1.7% CMC-Na + 2.5% PVA + 15% Al) was selected as the dispersion medium in subsequent experiments.
[0098] Experimental Example 6
[0099] With the core-shell droplet diameter, glass capillary diameter, and dispersed and continuous phase fluids remaining constant, droplet size control can be achieved by adjusting the flow rate ratio of the dispersed and continuous phases. Since this experiment involved coating the CeSi2 core with a fixed flow rate (v... d This is carried out under conditions where the continuous phase flow rate (v) is adjusted. c ), making v c / v d The ratio is adjusted between 5 and 10, increasing by 1 with each adjustment. After adjusting the continuous phase flow rate, wait for the droplet shear to stabilize and then collect a sufficient number of loaded droplets. Figure 14 The gel microspheres were solidified, and the diameter of the microdroplets was measured under an optical microscope and the average value was calculated. The relationship between the experimentally obtained gel microspheres and the flow rate ratio is as follows: Figure 15 As shown. Keeping the dispersed phase flow rate constant, the diameter of the loaded droplets varies with v. c / v d As the thickness of the core-shell structure increases or decreases, the thickness of the crust increases or decreases accordingly, thereby achieving controllable adjustment of the thickness of the microsphere shell.
[0100] Electron microscopy images of cross-sectional areas of gel microspheres prepared at different flow rate ratios are shown below. Figure 16 As shown, the Al shell thickness varies significantly with the flow rate ratio, but the thickness distribution is uneven. Analysis suggests this is because the CeSi2 core shifts position due to density differences before the shell solidifies. Specifically, there is a time lag between droplet shear generation, entry into the coagulation bath, and complete solidification of the shell liquid. Within this time window, the CeSi2 core, with a significantly higher density than the shell fluid, settles under the dominant force of gravity, causing it to deviate from the center and shift towards the bottom of the droplet, resulting in a "bottom eccentricity" phenomenon. These results indicate that the current process has initially achieved controllable preparation of the core-shell thickness.
[0101] Experimental Example 7
[0102] Experimental Example 6 showed that the optimal stability of the loaded droplet formation was achieved when the ratio of the continuous phase to the dispersed phase flow rate was fixed at 8 (dispersed phase flow rate 150 μL / min, continuous phase flow rate 1.2 mL / min). The loaded droplets obtained under these conditions were collected, solidified, calcined, and sintered to obtain the following... Figure 17 (a) shows the core-shell structured microspheres. Since it is difficult to directly measure the actual surface area of the microspheres and the surface area of an ideal sphere of equal volume to obtain theoretical sphericity, a simplified definition of two-dimensional projective sphericity was used for evaluation: the ratio of the maximum to the minimum diameter of 50 core-shell microspheres was statistically analyzed, yielding a sphericity of 0.96, indicating good sphericity. Fifty microspheres were randomly selected, and the average particle size was measured to be 350 μm, with a coefficient of variation (CV) of 4.5% and an average shell thickness of 35 μm. Comparison with the diameter of the corresponding gel microspheres shows that the average linear shrinkage rate from gel microspheres to the final sintered microspheres was 15.3%. The density of the sintered core-shell microspheres was determined using the water displacement method, showing an average apparent density of 3.16 g / cm³. 3 Its theoretical density (4.04 g / cm³) 3 Compared to the previous method, the relative density reached 78.3% TD (theoretical density percentage). This result indicates that the overall density of the microspheres is good under the current processing conditions.
[0103] Scanning electron microscopy (SEM) morphology of the outer shell of CeSi2 / Al core-shell structured microspheres is as follows: Figure 17 As shown in (b), after calcination to remove organic impurities and high-temperature densification, the shell layer exhibits a porous morphology. The overall sphericity is consistent with the observation results under an optical microscope, but the surface has slight undulations. The reason for this morphology is as follows: In order to ensure the chemical stability of aluminum powder in the composite dispersion medium and the smooth melting of the shell layer during the subsequent core pressing process, micron-sized powder was selected in this experiment instead of nano-sized aluminum powder. At the same time, the grinding and dispersion process only aims at the dissociation of agglomerated particles and does not further refine them. Therefore, after the gel material is calcined and removed, the aluminum shell layer will exhibit a more obvious porous structure.
[0104] SEM morphology and EDS elemental distribution of CeSi2 / Al core-shell structured microspheres are shown in the figure. Figure 18 As shown, from Figure 18 (a) The cross-sectional morphology shows that the microspheres exhibit obvious core-shell structure characteristics, with a clear interface between the core and the shell. Figure 18 (b) shows that Al elements are uniformly distributed in the shell region, while Figure 18 (c) Figure 18In (d), Ce and Si elements are concentrated in the core region, and their complementary distribution indicates that the core is the CeSi2 phase and the shell is the Al phase. The Ce element distribution in the figure is not very clear; the bright areas at the edges of the distribution map represent the conductive metal medium in the embedding material. This may be because the core and shell are not kept on the same plane, preventing the electron beam from focusing on both regions simultaneously. Furthermore, the finer CeSi2 powder particles may have entered the pores of other regions during embedding, sample preparation, and polishing, further interfering with the clarity of the element distribution. At the core-shell interface, the signal intensities of Al, Ce, and Si show a gradual transition, without sharp abrupt changes or intermediate phase aggregation, indicating good interfacial compatibility between the core and shell, with no obvious chemical reaction layer or diffusion layer. This helps maintain the independent properties of the core and shell while ensuring the interfacial bonding strength.
[0105] In summary, this invention successfully achieved the controllable preparation of CeSi2 / Al core-shell structured microspheres. The main conclusions are as follows: (1) Through rheological performance testing and droplet generation experiments, the optimal shell phase dispersion formulation was selected: 1.7wt% CMC-Na + 2.5wt% PVA + 15wt% Al. This formulation is highly equivalent to the rheological behavior of pure CMC-Na solution and can simultaneously meet the dual requirements of microsphere focusing and shell coating. (2) The focusing and aligning flow channel and the microfluidic shell coating module were integrated to design an integrated "alignment-coating" device. The single-droplet encapsulation capability was verified using a transparent shell phase dispersion, and the feasibility of the process was confirmed using an aluminum-containing actual dispersion. (3) The shell thickness was controllably adjusted by regulating the two-phase flow rate ratio. As the flow rate ratio increased, the diameter of the loaded droplets decreased, and the shell thickness became thinner. At the optimal flow rate ratio, the core-shell microspheres obtained had an average particle size of 350 μm, a shell thickness of 35 μm, a CV of 4.5%, and a sphericity of 0.96. Due to the high density of the core, eccentricity occurred before the shell solidified, resulting in the need to improve the uniformity of the core-shell microsphere thickness. (4) The average linear shrinkage rate from gel microspheres to the final sintered microspheres was 15.3%. The average apparent density of the microspheres measured by the water displacement method was 3.16 g / cm³. 3 The density was 78.3% TD. SEM and EDS analyses showed a clear interface between the core (CeSi2) and the shell (Al), with complementary elemental distributions, and the shell exhibited a porous granular morphology. This demonstrates the feasibility of a novel process for preparing high-density CeSi2 / Al core-shell structured simulated fuel microspheres, providing a new approach for the preparation of high-density core-shell structured fuel microspheres.
[0106] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A controllable preparation method for CeSi2 / Al core-shell structured microspheres, characterized in that, Includes the following steps: Step 1: CeSi2 microspheres are mixed with CMC-PVA-aluminum powder dispersion medium to obtain a dispersed phase. The dispersed phase flows sequentially through a straight + wave-shaped microsphere arrangement tube and a capillary tube. After the dispersed phase flows out of the capillary tube, it is sheared by the continuous phase in the three-way valve to form core-shell structured droplets. Then, it flows out through the liquid outlet tube into the coagulation bath. The three-way valve is sleeved on the capillary tube, and the straight + wave-shaped microsphere arrangement tube is placed vertically. Step 2: The outflowing structural droplets are allowed to stand in a coagulation bath, filtered, and the filtrate is removed. The precipitate is washed successively with petroleum ether and anhydrous ethanol, air-dried, and calcined under inert gas protection to obtain CeSi2 / Al core-shell structured microspheres.
2. The controllable preparation method of CeSi2 / Al core-shell structured microspheres according to claim 1, characterized in that, In step one, the volume fraction of CeSi2 microspheres in the dispersed phase is 5%, the particle size of the CeSi2 microspheres is 100-600 μm, and the density is 4-5 g / cm³. 3 .
3. The controllable preparation method of CeSi2 / Al core-shell structured microspheres according to claim 1, characterized in that, The CMC-PVA-aluminum powder dispersion medium described in step one comprises, by mass percentage, 1.5-2% CMC-Na, 0.5-5% PVA and 15% aluminum powder, with the balance being water.
4. The controllable preparation method of CeSi2 / Al core-shell structured microspheres according to claim 3, characterized in that, The preparation method of the CMC-PVA-aluminum powder dispersion medium is as follows: water and aluminum powder are mixed, the temperature is controlled by ice water, the resulting aluminum powder dispersion is mixed with PVA solution and CMC-Na solution respectively, the components are adjusted to the target mass fraction, and the mixture is stirred at low temperature.
5. The controllable preparation method of CeSi2 / Al core-shell structured microspheres according to claim 1, characterized in that, The continuous phase described in step one is dimethyl silicone oil.
6. The controllable preparation method of CeSi2 / Al core-shell structured microspheres according to claim 1, characterized in that, The coagulation bath described in step one comprises, by weight percentage, 74-75% dimethyl silicone oil, 24-25% isoamyl alcohol, and 1% boric acid.
7. The controllable preparation method of CeSi2 / Al core-shell structured microspheres according to claim 1, characterized in that, In step one, the flow rate ratio of the continuous phase to the dispersed phase is 6-10.
8. The controllable preparation method of CeSi2 / Al core-shell structured microspheres according to claim 1, characterized in that, The linear + wave-shaped microsphere arrangement tube in step one is a polytetrafluoroethylene tube with an outer diameter of 1600 μm and an inner diameter of 1000 μm, and is composed of a horizontal linear tube and a sinusoidal wave tube. The dispersed phase flows in through the horizontal linear tube and flows out through the sinusoidal wave tube. The capillary is a glass tube with an outer diameter of 670 μm and an inner diameter of 450 μm. The tee is a T-type tee, and the continuous phase flows in through the vertical port. The liquid outlet tube is a polytetrafluoroethylene tube with an outer diameter of 1600 μm and an inner diameter of 1000 μm.
9. The controllable preparation method of CeSi2 / Al core-shell structured microspheres according to claim 1, characterized in that, In step two, during the calcination process, the temperature is increased to 150℃ at a rate of 2℃ / min and held for 2 hours. Then, the temperature is increased to 350℃ at a rate of 5℃ / min, and then increased to 500℃ at a rate of 1℃ / min and held for 2 hours. Finally, the temperature is increased to 650℃ at a rate of 5℃ / min and held for 1 hour to obtain the final product.
10. CeSi2 / Al core-shell structured microspheres prepared by the method according to any one of claims 1-9.